Hubungan Nilai Ujian Nasional Matematika dengan Indeks Prestasi Kumulatif Mahasiswa Program Studi Tadris Matematika Fakultas Tadris Umum - Zaif Zairozie, Athar; Hidayatillah, Wahyu; Nasikhah, Jamiatun (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
ABSTRACT This study used descriptive quantitative research. The purpose of this research is to find a National Math Test and the Grade Point Average (Indeks Prestasi Kumulatif) students of Program Study Tadris Mathematika, Fakultas Tadris Umum in University Islam Zainul Hasan Genggong. All students of this Program are the populations and 22 students is taken from them with random sampling as the sampler of the research. The Data collectionis collected by documents technique. While the data is analyzed by product moment korelation analysis on SPSS aplicationt. The analisis showed sig. (2 tailed) = 0,937 > = 0,05; so that H0 received. It means there is no relation between National Math Test and the Grade Point Average . Keyword: National Math Test, the Grade Point Average